Autobiographical Memory Functions Served by Multiple Event Types. Issue 2 (19th November 2013) - Waters, Theodore E. A.; Bauer, Patricia J.; Fivush, Robyn
Summary Autobiographical memories are thought to serve three basic functions: self‐definition, social connection, and directing future behavior. Previous research suggests that the function a memory comes to serve may differ by the type of event recalled (e.g., single unique events vs. repeated or recurring events). In two studies, we compared memories for different event types on function served. Results from Study 1 suggest that narratives of single events serve more of a self and directive function compared with recurring events, whereas recurring events serve more of a social function. Extended events, however, were high on all three functions. Study 2 specifically examined single and recurring events. Results replicated and extended Study 1 using both narrative coding and questionnaire measures. Implications of the examination of multiple event types and functional approaches to autobiographical memory for understanding links between experiences and psychological outcomes are discussed. Copyright © 2013 John Wiley & Sons, Ltd.